Journal of Complementary and Integrative Medicine (De Gruyter, 2004)
The Journal of Complementary and Integrative Medicine focuses on evidence concerning the efficacy and safety of complementary and alternative medical (CAM) whole systems, practices, interventions and natural health products, including herbal medicines.